1996
DOI: 10.1161/01.str.27.6.1028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Malnutrition After Acute Stroke on Clinical Outcome

Abstract: Our findings suggest that protein-energy malnutrition after acute stroke is a risk factor for poor outcome. Early appropriate enteral caloric feeding did not prevent malnutrition during the first week of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
254
3
20

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(285 citation statements)
references
References 23 publications
8
254
3
20
Order By: Relevance
“…Previous studies reported significantly lower frequency of hypoalbuminemia in stroke patients. Davalos et al (1996) assessed malnutrition in 104 patients with acute ischemic and hemorrhagic stroke. Serum albumin level was measured within 24 h after stroke onset, and hypoalbuminemia (serum albumin level o35 g/l) was observed in 7.7% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported significantly lower frequency of hypoalbuminemia in stroke patients. Davalos et al (1996) assessed malnutrition in 104 patients with acute ischemic and hemorrhagic stroke. Serum albumin level was measured within 24 h after stroke onset, and hypoalbuminemia (serum albumin level o35 g/l) was observed in 7.7% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia was reported in up to 19% of stroke patients (Davalos et al, 1996;Gariballa et al, 1998;Davis et al, 2004). Stroke patients with hypoalbuminemia at admission had increased risk of infective complications (Gariballa et al, 1998;Dziedzic et al, 2006), death (Gariballa et al, 1998;Davis et al, 2004) and poor functional outcome (Davalos et al, 1996;Gariballa et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…after the second week of admission (Davalos et al, 1996). Even early aggressive enteral nutrition did not prevent malnutrition developing during the first week of admission for patients with impaired swallowing.…”
Section: Case Illustrationmentioning
confidence: 85%
“…28 Weight loss often coincides with malnutrition in the setting of critical illness, leading to increased risk of poststroke complications, 29 including gastrointestinal bleeding, pneumonia, and other infections. 29,30 Acute stroke patients who are malnourished are at risk for poorer outcomes, 28 independent of baseline nutritional status and age, [29][30][31] and are also at risk for continued undernourishment during hospitalization. 32 Patients with eating difficulties on admission have been shown to require longer hospital admissions and are more likely to require institutionalized care following discharge.…”
Section: Weight Loss and Malnutritionmentioning
confidence: 99%